SWOT Analysis in the Development of Long-Term Strategy asa Strategic Evaluation for Business Implementation Success - Riadi Abd. Fatah; Muhamad Rizqi Adi Nugraha; Mulyadi Mulyadi; Mohamad Samsudin; Hadi Supratikta (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
SWOT analysis is a crucial tool in the development of long-term strategies and strategic evaluation in the business world. This study aims to explore the application of SWOT analysis in identifying the strengths, weaknesses, opportunities, and threats faced by businesses in formulating long-term strategies. Through SWOT analysis, companies gain valuable insights into both internal and external factors that influence the success of business strategy implementation. This research uses a literature review approach to examine various theories and relevant case studies that demonstrate the effectiveness of SWOT as a strategic evaluation tool. The findings indicate that SWOT analysis is not only useful in determining a company’s market position but also in assisting management in formulating policies that are adaptable to changing business environments. Furthermore, this study highlights the importance of integrating SWOT analysis with other strategic planning processes to achieve long-term success. Therefore, SWOT analysis proves to be an effective instrument in assessing and developing business strategies to achieve optimal implementation success.